The level of football analysis on the optimal development phase (Golden Age) of adolescents aged 13 to 17 years - Adelia Utama Bastian; Reza Adhi Nugroho (SAINTIS Publishing, 2025)
Football is one of the sports that can support physical, mental, and social development, especially during the optimal development period (golden age) of adolescents. This period, which occurs at the age of 13-17, is an important period in physical development and motor skills. This study aims to analyze the influence of football on the optimal development of adolescent girls in this age range. The study used the cross-cutting method by involving 60 adolescent girls who actively participated in football training at a football school in Central Java. The data collected included physical development (height, weight, and nutritional status based on BMI/age), motor development (balance, agility, and muscle strength), and social development (team interaction and confidence). The results showed that participation in football had a significant influence on physical (p0.05), motor (p0.01), and social (p0.01) development. This study concludes that football provides positive benefits during the optimal development period of adolescent girls, especially in physical, motor, and social aspects. Longitudinal studies with larger population coverage are needed to identify appropriate exercise strategies to maximize progression without increasing the risk of injury.